PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN STRATEGI REACT TERHADAP KEMAMPUAN KONEKSI MATEMATIK SISWA MATERI DIMENSI TIGA KELAS X SMA - Dwi Sulistyaningsih; Martyana Prihaswati (Universitas Muhammadiyah Semarang, 2015)
Aim of this study was to develop learning tools of mathematics by model of Experiencing, Applying, Cooperating, and Transferrin (REACT) which was valid and practical. Learning tools developed include syllabi, lesson plan, Student Worksheet, and the student book. The development refers to the Plomp models of development model of learning device, which consists of five phases, namely the initial investigation phase, the design phase, the phase of realization, evaluation and revision of the test phase. The research instruments used in this study were the validation sheet of learning tools, questionnaire sheet of student responses to the learning implementation, and questionnaire sheet of teacher responses to the learning tools. Validator assessment results indicate that the learning tools developed were valid with an average value for validation of syllabus, lesson plans, student worksheets, and the student book were 3.23 (good), 3.21 (good), 3.29 (very good), and 3.39 (very good), respectively. Field trials showed that the application of the learning tools developed was practical. A total of 82.40% of students responded positiv to the application of the learning tool in class, while the teacher assess that learning tool that is used with a value of 4.29 (good criteria)Keywords: React, lerning tool, mathematical connection, three-dimensional